Role of microglia in brain development after viral infection - Xu, Pei; Yu, Yongjia; Wu, Ping (Frontiers in Cell and Developmental Biology, 2024)
Microglia are immune cells in the brain that originate from the yolk sac and enter the developing brain before birth. They play critical roles in brain development by supporting neural precursor proliferation, synaptic pruning, and circuit formation. However, microglia are also vulnerable to environmental factors, such as infection and stress that may alter their phenotype and function. Viral infection activates microglia to produce inflammatory cytokines and anti-viral responses that protect the brain from damage. However, excessive or prolonged microglial activation impairs brain development and leads to long-term consequences such as autism spectrum disorder and schizophrenia spectrum disorder. Moreover, certain viruses may attack microglia and deploy them as "Trojan horses" to infiltrate the brain. In this brief review, we describe the function of microglia during brain development and examine their roles after infection through microglia-neural crosstalk. We also identify limitations for current studies and highlight future investigated questions. .This minireview outlines the role of microglia in brain development and their function following infection (Figure 1). It also discusses limitations in current research and suggests areas for future investigation.